Tough Conversations: Development of a Curriculum for Medical Students to Lead Family Meetings. (December 2017) - Hagiwara, Yuya; Ross, Jeanette; Lee, Shuko; Sanchez-Reilly, Sandra
Background: Few educational interventions have been developed to teach Family Meeting (FM) communication skills at the undergraduate level. We developed an innovative curriculum to address this gap. Methods: Fourth year medical students during 2011-2013 (n = 674) completed training for conducting a FM. To assess the effectiveness of this training, students completed a FM Objective Structured Clinical Exam (OSCE) that included 15 domains rated on a 1-5 point Likert scale. Tasks included discussing prognosis, establishing goals of care and demonstrating conflict resolution skills. Students received one-to-one feedback from standardized family members and faculty observers. Group debriefings with faculty were held after the OSCE. Results: Analysis of faculty feedback narratives revealed four themes in which students required improvement: 1) Discussing prognosis, 2) Explaining palliative care/hospice, 3) Avoiding medical jargon, and 4) Discussing cultural/religious preferences. Evaluation total mean score was 28.2 (Min 15, Max 63; SD 7.57), and identified student's need to; 1) Ask more about the degree of knowledge family members want, 2) Ask religious beliefs, and 3) Assess family members' level of education ( p < 0.001). Qualitative analysis of group debriefings suggested that student perception of the OSCE experience was positive overall. Students found the case to be realistic and immediate feedback to be helpful. Conclusions: Conducting a FM is an advanced skill. This study shows that it is possible to train fourth year students to lead FMs and identify their strengths, needs using a FM OSCE.